Validity and Reliability in Autonomy Needs Scale for Student - A’zam, Muhammad Nazif; Husna, Aftina Nurul; Qomariyah, Laili (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2023)
The need for autonomy is how the individual thinks that his behaviour comes from himself without being influenced by others. The formation of autonomy was influenced by seven aspects, namely freedom, initiative, self-confidence, responsibility, self-assertiveness, decision-making, and self-control. The purpose of this study is to determine the validity and reliability of the scale of autonomy needs that are made. This article also to explain specifically about the need for autonomy because there are not many articles that explain about autonomy needs of student. This research involved 92 students from various cities and universities to become subjects. The questionnaire consists of 60 items designed to assess aspects of freedom, initiative, self-confidence, responsibility, self-assertiveness, decision-making and self-control. This questionnaire has five alternative answers, namely 1 for "Strongly Disagree", 2 for "Disagree", 3 for "Somewhat Agree", 4 for "Agree", and 5 for "Strongly Agree". The results of this study indicate that it takes three rounds to find the level of validity and reliability on this scale with Cronbach's alpha of 0.937 and the number of items as many as 22 item. This research is expected to provide insight regarding the need for autonomy and it is hoped that research on the scale of this need for autonomy can be further developed in subsequent studies.